Preparation and characterization of magnesium hydroxyapatite coatings on 316L stainless steel - Hanh, Vo Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Thom, Nguyen Thi; Phuong Thao, Le Thi; Mai Thanh, Dinh Thi (Vietnam Journal of Chemistry, 2017)
Magnesium hydroxyapatite coatings (MgHAp) were deposited on the surface of 316L stainless steel (316L SS) substrates by electrodeposition technique. Diﬀerent concentrations of Mg2+ ion were incorporated into the apatite structure by adding Mg(NO3)2 into electrolyte solution containing 3×10-2 M Ca(NO3)2, 1.8×10-2 M NH4H2PO4 and 6×10-2 M NaNO3. With Mg2+ concentration 1×10-3 M, the obtained coatings have 0.2 wt% Mg2+. The influences of scanning potential ranges, scanning times to deposit MgHAp coatings were researched. The analytical results FTIR, SEM, X-ray, EDX, thickness and adhension strength showed that MgHAp coatings were single phase of HAp, fibrous shapes, thickness 8.1 µm and adhesion strength 7.20 MPa at the scanning potential ranges of 0÷-1.7 V/SCE and scanning times of 5 scans. Keywords. 316L SS, Electrodeposition, MgHAp.